Peran Badan Usaha Milik Desa (BUMDes) dalam Peningkatan Kesejahteraan Masyarakat Di Desa Ponggok, Kabupaten Klaten - Fajar Subehi; Asma Luthfi; Moh. Solehatul Mustofa; Gunawan Gunawan (Umbara, 2018)
Desa Ponggok is one of the independent villages in Indonesia. This village can manage its natural potential through Village-Owned Enterprises (BUMDes) to improve welfare and empower its society. This research describes in detail the efforts made by the government and villagers in improving welfare through various businesses managed under BUMDes. This research uses qualitative, descriptive methods. Data collection techniques are carried out through involved observation, in-depth interviews, and documentation. This study found that managing the assets and potential of the village through BUMDes Tirta Mandiri which involved the village community had succeeded in improving the welfare of the residents was not simple. Several factors hinder and encourage the success of this effort, including technology, human resources, and business competition. However, a solid collaboration between the government and villagers has proven to be able to overcome obstacles and make BUMDes as facilitators in the socio-economic empowerment of its citizens.